Gestão do comportamento informacional apoiada na cultura organizacional e em modelos mentais - Cavalcante, Luciane de Fátima Beckman [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The information and the individuals pass all tasks and process organizational is possible direct studies to the organizational context, in what understand and identify the way as the individuals work the information. Is relevant understand like the individual develops certain behaviors regarding the information, what implies in do an analysis this organizational actor under an cognition approach, because the informational behavior triggered by him can derive from process and representations presents in the individual mind. To present research aimed at analyze, in a cellulose manufacturing company, the relation between the individuals informational behavior and the TICs, focusing cognitions aspects that triggered such behavior, as the mental models, with objective of to propose a systemization to the managment of informational behavior returned to the technologies of information and communication applied to the business environments. To research was supported by twenty participants of distinct organizational levels of a cellulose manufacturing company in the São Paulo State. The methodological procedures were supported by the Laurence Bardin method, called 'Content Analysis', more specifically applying the technical 'Categories Analysis'. Were elaborate and utilized as data collecting instrument, the structured questionnaire and the structured interview. The results obtained provided to identify the individual mental representations that the researched possess about the informational behavior informacional, and understand how the organizational culture / informational culture can interfere in that behavior. It was possible verify, also, that the research individuals participants conceive the TICs as a tool that helps the activities developed in the company, motivating the way as the information flowed in the organizational environment. Believes that the arguments... (Complete abstract click electronic access below)

Uma vez que a informação e os indivíduos perpassam todas as tarefas e processos organizacionais é possível direcionar estudos ao contexto organizacional, no que tange a compreender e identificar o modo como os indivíduos trabalham a informação. É relevante compreender como o indivíduo desenvolve certos comportamentos em relação à informação, o que implica em fazer uma análise desse ator organizacional sob um enfoque cognitivo, porquanto o comportamento informacional desencadeado por ele pode derivar de processos e representações presentes na mente do indivíduo. A presente pesquisa visou analisar, em uma empresa de fabricação de celulose, a relação entre o comportamento informacional dos indivíduos e as TICs, enfocando os aspectos cognitivos que desencadeiam tal comportamento, tais como os modelos mentais, com intuito de propor uma sistematização à gestão de comportamento informacional voltado às tecnologias de informação e comunicação aplicado aos ambientes empresariais. A pesquisa contou com um total de vinte participantes de distintos níveis organizacionais de uma empresa de fabricação de celulose localizada no interior do Estado de São Paulo. Os procedimentos metodológicos foram apoiados pelo método de Laurence Bardin, denominado ‘Análise de Conteúdo’, mais especificamente aplicando a técnica ‘Análise Categorial’. Foram elaborados e utilizados como instrumento de coleta de dados, o questionário estruturado e a entrevista semi-estruturada. Os resultados obtidos propiciaram identificar as representações mentais que os indivíduos pesquisados possuem acerca do comportamento informacional, bem como compreender como a cultura organizacional/cultura informacional pode interferir nesse comportamento. Foi possível verificar, também, que os indivíduos participantes da pesquisa concebem as TICs...
Keywords: Cultura organizacional; Comportamento informacional; Cultura informacional; Informational behavior; Informational culture; Organizational culture; Cognition; Technologies of information and communication (TICs)